Pax troikana: the U.K. media and the symbolic conflicts of the Cypriot ‘rescue’ programme - Airaghi, Giulia; Avraamidou, Maria (My University, 2017)
This chapter, by exploring tacit meanings and ideas in two mainstream news media, The Guardian and The Telegraph it explicates the U.K. media’s reaction to the Cypriot ‘bailout’ as a symbolic conflict (of policies, ideologies and interests). Therefore, it illustrates dominant and less dominant ideological positions in the U.K. media and links them not only to the handling of the Cypriot crisis, but also to the U.K.’s (re)positioning in its controversial relations with the EU.
Keywords: Cyprus; Memorandum of Understanding; European Central Bank; European Commission; International Monetary Fund; Economic crisis; Hegemony; Media